Immunohistochemical and morphological features of a small bowel leiomyoma in a black crested macaque (Macaca nigra) - Aristizabal-Arbelaez, Monica; Mejia-Restrepo, Julian; Montoya-Florez, Mauricio [UNESP]; Grandi, Fabrizio [UNESP]; Pedraza-Ordonez, Francisco [UNESP] (Biomed Central Ltd., 2012)
Background: Spontaneous gastrointestinal neoplasms in non-human primates are commonly seen in aged individuals. Due to genetic similarities between human and non-human primates, scientists have shown increasing interest in terms of comparative oncology studies.Case presentation: The present study is related to a case of an intestinal leiomyoma in a black crested macaque (Macaca nigra), kept on captivity by Mateca a Zoo, Pereira City, Colombia. The animal had abdominal distension, anorexia, vomiting, diarrhea and behavioral changes. Clinical examination showed an increased volume in the upper right abdominal quadrant caused by a neoplastic mass. The patient died during the surgical procedure. Necropsy revealed several small nodules in the peritoneum with adhesion to different portions of the small and large intestines, liver, stomach and diaphragm. Tissue samples were collected, routinely processed and stained by H&E. Microscopic examination revealed a mesenchymal tumor limited to tunica muscularis, resembling normal smooth muscle cells. Neoplastic cells were positive for alpha-smooth muscle actin and vimentin, and negative for cytokeratin AE1/AE3 by immunohistochemistry. Those morphological and immunohistochemical findings allowed to diagnose the intestinal leiomyoma referred above.Conclusion: Neoplastic diseases in primates have multifaceted causes. Their manifestations are understudied, leading to a greater difficulty in detection and measurement of the real impact provides by this disease.
Keywords: Neoplasm; Small bowel; Macaca; Monkey; Leiomyoma; Intestine